School Counselor Professional Competence (PC-SC): Social Media Utilization in Guidance and Counselling Services (GC-S) - Putri, Tesa Restika; Supriyanto, Agus; Martaningsih, Sri Tutur; Rosada, Ulfa Danni (Counsellia: Jurnal Bimbingan dan Konseling, 2022)
The school counselling profession has challenges in pandemic or post-Covid-19 pandemic conditions for self-development and alleviation of student problems. Current conditions limit all access to learning as well as GC-S (GC-S). The social media utilization becomes an alternative supporting GC-S. The goal of this research is to evaluate the use of social media by school counsellors to support GC-S in schools. Mix-method research with sequential transformative design through quantitative data backed by qualitative data. The research targets were 90 students and three school counsellors with questionnaires and interviews. Analysis of questionnaire data was quantitative with standard deviation and percentage, and then interview data was descriptive qualitative. The result of the study is that school counsellors have used social media to support GC-S with good categories. School counsellors use two primary social media, namely WhatsApp and YouTube, because of the access and convenience for students, although not all students can interact, discuss, and participate actively. Counsellors need to be more active and creative during a pandemic or post-Covid-19 pandemic in GC-S with various technologies in GC-S.